2021
DOI: 10.3390/aerospace8070186
|View full text |Cite
|
Sign up to set email alerts
|

Water Recognition on the Moon by Using THz Heterodyne-Spectrometer for Identifying the Appropriate Locations to Extract Water for Providing Oxygen for Breathing and Fuel for Spaceships’ Propulsion on the Moon with CubeSat

Abstract: Asteroid mining offers vital sources for improving human lives and provides opportunities for interplanetary missions and space travel. There are many professional commercial space companies that are only investing billions of dollars on asteroids mining, but prior to that, one condition for asteroid mining could be planetary stations to refuel the pioneers’ spacecraft or human colonies on alien planets; hence, one of the vital sources for these purposes is water. Water can be harvested to split oxygen for bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The concepts arising from this insightful speech suggest that space colonization is a vital investment for the long-term survival of humanity [30]. As the sun's energy is finite, with estimates suggesting it will die out in the next 5 billion years, it is logical to begin taking preventive measures now to ensure humanity's future [31]. To create life on an extraterrestrial planet, water is a vital element there.…”
Section: Design Methodologymentioning
confidence: 99%
“…The concepts arising from this insightful speech suggest that space colonization is a vital investment for the long-term survival of humanity [30]. As the sun's energy is finite, with estimates suggesting it will die out in the next 5 billion years, it is logical to begin taking preventive measures now to ensure humanity's future [31]. To create life on an extraterrestrial planet, water is a vital element there.…”
Section: Design Methodologymentioning
confidence: 99%
“…It should be noted that the mothership utilizes an active THz radiometer to perform active remote sensing of the Mars atmosphere; therefore, the mothership can collect data day and night; it gives a new objective to the Mars orbiter. Research indicates that THz devices can determine the total thickness and shapes of clouds [77], and previous studies have shown that Mars' atmospheric water vapor averages around 1% [78]. Therefore, we propose the THz radiometer as a scientific mission to scan the Martian atmosphere and give us new, as yet undefined, data from the Martian atmosphere.…”
Section: The Mission Scientific Payload: Usage Of Thz Radiometer For ...mentioning
confidence: 99%
“…Another example is [27], which makes a review on 130 CubeSat missions, grouped depending on their main goal: Astrophysics, Deep Space Exploration, Earth Science, Heliophysics: Space Weather, Spaceborne In Situ Laboratory, and Technology Demonstration. Some examples are missions to perform asteroid mining and a Lunar CubeSat Injector to identify locations of water sources on the Moon with the help of a spectrometer [28], and missions to quantify dust particles in orbit [29].…”
Section: The Cubesat Paradigmmentioning
confidence: 99%